Immigration, Drinking, and Frequent Mental Distress - Julius Ade MD, PhD; James E. Rohrer PhD; Munira Merchant MSW, PhD (SAGE Publishing, 2010)
Objective: The objective of this study was to investigate the importance of immigration as a risk factor for self-reported frequent mental distress (FMD) among black respondents to an Internet survey. Method: Snowball sampling was used to obtain Internet survey responses from immigrant and non-immigrant black adults in the United States. Multiple logistic regression analysis was used to control for the effects of personal characteristics ( N = 301). Results: In this sample of black adults, 13.3% had FMD. Being an immigrant was not associated with FMD in this sample (adjusted odds ratio [OR] = 0.75, P = .53). However, more drinking days was an independent risk factor (OR = 1.07, P < .01). Conclusions: Being an immigrant was not an independent risk factor for FMD in this sample of black adults. However, drinking more days per month was a significant risk factor. Primary care providers should be alert for FMD and alcohol consumption in this population. Directing health education about hazardous drinking toward high-risk individuals should be considered.